Using AMS and Palaeomagnetic Data to Assess Tectonic Rotation: A Case Study from Savannah Nickel Mine, WA. Issue 1 (1st December 2018) - Austin, Jim; Patterson, Ben
Abstract : Recent research has shown that Ni-PGE mineralisation is typically associated with specific intrusion types, e.g., chonoliths, bladed-dykes and funnels that acted as high-throughput magma conduits within much larger magmatic provinces. The initial architecture of these systems is very different, but additional structural modification during orogenesis can render such intrusions very difficult to understand structurally, and hence make it very difficult to target the fertile zones within the system. In structural geology it is common to evoke shortening directions, which are assumed to apply to all rocks regardless of their rheology. This is not realistic. Furthermore, resolving the partitioning of strain is not straightforward for intrusive rocks, which tend not to develop visible tectonic fabrics, but act as rigid blocks that rotate to accommodate strain, rather than compress or shear, during deformation. Unfortunately there are few structural techniques that can be used to quantify such rotation. Intrusions near the Savannah Nickel Mine, East Kimberley, WA were observed to have different deformation histories, despite being temporally equivalent. In this study we measured anisotropy of magnetic susceptibility (AMS) and remanent magnetisation in two adjacent, temporally equivalent, intrusions. The observed K3 AMS vectors are typically normal to the magmatic layering in layered intrusions. Where K3 vectors sit along a great circle, the pole to that great circle indicates the rotation axis. Original palaeomagnetic vectors would be expected to be consistently oriented with respect to magmatic layering, and can be used similarly to test the consistency of the inferred rotation analysis. The rotations inferred for the intrusions tested were consistent between the two techniques. Savannah and Savannah North, were subjected to N-S, NE-SW and NW-SE shortening, consistent with the Halls Creek Orogeny. However, N-S shortening was dominant at Savannah and NE-SW dominant at Savannah North. Therefore, despite their equivalent emplacement ages and implied tectonic history, each intrusion has undergone very different deformation.